Experimental analysis and numerical simulation of melting process of vertical tin cladding. (June 2020) - Wang, Wanhong; Wang, Shuai; Peng, Changhong; Guo, Yun
Highlights: The melting process of the vertical tin cladding was experimentally and numerically observed. The influence of heating power, cladding thickness and environmental condition on the melting process was analyzed. The melting process in both experiments and numerical simulations was qualitatively compared. The cylindrical wall stress model was introduced to analyze the degree of swelling deformation. Abstract: The melting process of vertical tin cladding is experimentally and numerically studied. The influence of heating powers, cladding thicknesses and ambient conditions on the melting process was evaluated and the cylindrical wall stress model was introduced to analyze swelling deformation. Experimental results show the melting process can be divided into three stages: heating, melting and disintegration, and the melting stage can be subdivided into three sub-stages: droplet leaking, swelling deformation and cladding breakage. The stress model suggests swelling deformation and cladding breakage are affected by two mechanisms-metal melting and stress limit, the degree of swelling deformation depends on cladding thicknesses, and there is a negative correlation between the height of the breakage and the product of heating powers and melting time. Numerical results show the melting process can be divided into four stages: heating, melting, breakage and re-solidification, the occurrence of the cladding breakage is a turning point in the melting process, the breakage height is affected by ambient temperatures. The melting stage is guided by two heat transfers-the heat transfer from inside to outside and the heat transfer related to transporting the heat to the lower region by liquid tin flowing downward along the solid tin layer.